Enhance the voltage drop in the end costumer of PT. PLN ULP 50 Kota using insertion transformer - arif, Syafwanil; Habibullah (Department of Electrical Engineering Universitas Negeri Padang, 2024)
Loading that exceeds the capacity of the transformer if left unchecked will damage the transformer itself; apart from that, it can also cause drop voltage along the conductor, which causes electricity services to customers to be disrupted, especially at the customer end. The results of research at PT PLN (Persero) ULP 50 Kota Suliki Service Office revealed that of the 108 existing transformers, the GD 175 Kasiak Rampung transformer experienced overload with a percentage of 99%, and the end voltage measurement was 177 volts. This figure does not comply with the standards set by PLN. An insert transformer was built as an improvement effort so that the loading percentage decreased to 45% and the end voltage became 277 volts. This effort provides benefits, namely improving the quality of customer service, increasing electricity sales, reducing ENS if there are maintenance efforts, and improving the company's image.